The Archaeology and Ethnohistory of Walrus Ritual around Bering Strait - Hill, Erica (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
Nineteenth-century ethnohistoric sources describe rituals and beliefs related to the exploitation of walrus (Odobenus rosmarus) on the islands of the Bering Sea and the coast of Chukotka. These small-scale rites practiced by St. Lawrence Islanders, Siberian Yupiget, and Chukchi were intended to thank walrus and ensure future hunting success. Rituals conducted by walrus boat captains also facilitated integration of walrus hunting crews and their families. Archaeological evidence for the antiquity of walrus-related ritual is provided by concentrations of walrus skulls in structures and deposition of walrus bones in cemeteries. The centrality of walrus to subsistence, material culture, and ritual life of coastal peoples deserves more scholarly attention in both archaeological and historical reconstructions of Yupik and Chukchi multispecies pasts.